We are in the Same Boat: Group Therapy as a Treatment for Psychological Distress in Dating Violence Survivors - Pradipta Christy Pratiwi; Fatma Kusuma Mahanani; Tri Esti Budiningsih; Julian Adrian Halim (Universitas Ahmad Dahlan, 2022)
Young adults are synonymous with the task of developing intimacy. This phase is inseparable from the problem of dating violence. This situation is a social stressor that causes a negative stress response commonly known as psychological distress. The purpose of this study is to provide treatment for 5 young adults who have experienced dating violence with online group intervention. The intervention design was carried out for seven 60-90 minutes sessions. The evaluation was done using observation, DASS, and BDI-II. Friedman’s test showed a significant result for depression (BDI-II, χ2F = 6.533, p = .038; DASS, χ2F = 6.533, p = .038) and anxiety (χ2F = 6.000, p = .050), and a non-significant result for stress (χ2F = 3.500, p = .174).